On the role of REM sleep microstructure in suppressing interictal spikes in Electrical Status Epilepticus during Sleep. (April 2022) - Giacomini, Thea; Luria, Gianvittorio; D'Amario, Vanessa; Croci, Carolina; Cataldi, Matteo; Piai, Maria; Nobile, Giulia; Bruni, Oliviero; Consales, Alessandro; Mancardi, Maria Margherita; Nobili, Lino
Highlights: REM sleep has a suppressive effect on epileptic activity in Electrical Status Epilepticus during Sleep (ESES). REM sleep is made up of the alternation of Phasic REM (PREM) and Tonic REM (TREM) sleep. The spike index was reduced by 87 % in PREM with respect to TREM. Abstract: Objective: Non-Rapid Eye Movement (NREM) sleep promotes the spread and propagation of Interictal Epileptiform Discharges (IEDs), while IEDs are suppressed during REM. Recently, it has been shown that the inhibitory effect on epileptic activity is mostly exerted by the phasic REM (PREM) microstate. This study aims at assessing if this holds true even in the extreme condition of IEDs activation during sleep represented by Electrical Status Epilepticus during Sleep (ESES). Methods: eight patients affected by ESES, who underwent long-term EEG were included. REM was subdivided into phasic and tonic microstates along with the sleep scoring. IEDs count was carried out using a semi-automatic method and a Spike Index (SI) was calculated. Results: The SI was significantly higher in NREM sleep than in REM. Within REM, the SI was significantly lower in PREM than in tonic REM (TREM). The SI was reduced by 84 % in TREM with respect to NREM and by 97 % in PREM with respect to NREM. Moreover, the SI was reduced by 87 % in PREM with respect to TREM. Conclusions: PREM has a greater suppressive effect on epileptic activity even in the extreme IEDs activation during sleep typical of ESES. Significance: Understanding the protective effect of PREM sleep on epileptic activity might be relevant for future therapeutic approaches.